Dopaminergic signaling within the primary cilia in the renovascular system - Atkinson, Kimberly F.; Kathem, Sarmed H.; Jin, Xingjian; Muntean, Brian S.; Abou-Alaiwi, Wissam A.; Nauli, Andromeda M.; Nauli, Surya M. (Frontiers in Physiology, 2015)
Activation of dopamine receptor type-5 (DR5) has been known to reduce systemic blood pressure, most likely by increasing renal vasodilation and enhancing natriuresis in the kidney. However, the mechanism of DR5 in natriuresis and vasodilation was not clearly known. We have previously shown that DR5 is localized to primary cilia of proximal renal epithelial and vascular endothelial cells. We here show that selective activation of DR5 specifically induces calcium influx only in the primary cilia, whereas non-selective activation of dopamine receptor induces calcium fluxes in both cilioplasm and cytoplasm. Cilia-independent signaling induced by thrombin only shows calcium signaling within cytoplasm. Furthermore, calcium activation in the cilioplasm by DR5 increases length and mechanosensory function of primary cilia, leading to a greater response to fluid-shear stress. We therefore propose a new mechanism by which DR5 induces vasodilation via chemical and mechanical properties that are specific to primary cilia.